Optical tuning of polymer functionalized zinc oxide quantum dots as a selective probe for the detection of antibiotics - Awadhesh Kumar Verma; G. B. V. S. Lakshmi; Tarun Kumar Dhiman; S. Z. H. Hashmi; Anil Kumar; Pratima R. Solanki (Scientific Reports)
Abstract Excess consumption of antibiotics leads to antibiotic resistance that hinders the control and cure of microbial diseases. Therefore, it is crucial to monitor the antibiotic levels in the environment. In this proposed research work, an optical nano-sensor was devised that can sense the ultra-low concentration of antibiotics, in samples like tap water using fluorescent zinc oxide quantum dots (ZnO QDs) based nano-sensor. For this, different polymers (polyvinylalcohol–PVA and polyvinylpyrrolidine–PVP) capped florescent ZnO QDs were synthesized using a modified sol–gel technique. These were used as fluorescent probes to monitor the presence of antibiotics. The optical characterizations of synthesized QDs were performed using UV–visible absorption and fluorescence spectroscopic methods while structural characteristics were analyzed by using Raman spectroscopy and X-ray diffraction spectroscopy. The formation of capped QDs was confirmed by Fourier transform infrared spectroscopy (FTIR). Charge on the synthesized QDs was obtained with the help of ZETA potential. Here ten different antibiotics were checked, Ciprofloxacin and Moxifloxacin have shown excellent sensing and specificity with PVA-ZnO QDs and PVP-ZnO QDs with LOD of 1.4 nM and 0.8 nM, and sensitivity of 36.17 units/mM and 19.33 units/mM respectively. This study also inferred the tuning of the ZnO QDs properties and specificity towards the different antibiotics can be achieved by capping QDs with different polymers.